Vaccination against influenza in rheumatoid arthritis: the effect of disease modifying drugs, including TNFα blockers. Issue 2 (13th July 2005) - Fomin, I; Caspi, D; Levy, V; Varsano, N; Shalev, Y; Paran, D; Levartovsky, D; Litinsky, I; Kaufman, I; Wigler, I; Mendelson, E; Elkayam, O
Abstract : Objective: To assess the efficacy and safety of vaccination against influenza virus in patients with rheumatoid arthritis, with special emphasis on the effect of disease modifying antirheumatic drugs (DMARDs), including tumour necrosis factor α (TNFα) blockers. Methods: 82 rheumatoid patients and 30 healthy controls were vaccinated with a split-virion inactivated vaccine containing 15 μg haemagglutinin (HA) per dose of each of B/Hong Kong/330/2001 (HK), A/Panama/2007/99 (PAN), and A/New Caledonian/20/99 (NC). Disease activity was assessed by tender and swollen joint count, morning stiffness, evaluation of pain, Health Assessment Questionnaire, ESR, and C reactive protein on the day of vaccination and six weeks later. Haemagglutination inhibiting (HI) antibodies were tested by a standard WHO procedure. Response was defined as a fourfold or more rise in HI antibodies six weeks after vaccination, or seroconversion in patients with a non-protective baseline level of antibodies (<1/40). Geometric mean titres (GMT) were calculated to assess the immunity of the whole group. Results: Six weeks after vaccination, a significant increase in GMT for each antigen was observed in both groups, this being higher in the healthy group for HK (p = 0.004). The percentage of responders was lower in rheumatoid patients than healthy controls (significant for HK). The percentage of responders was not affected by prednisone or any DMARD, including methotrexate, infliximab, and etanercept. Indices of disease activity remained unchanged. Conclusions: Influenza virus vaccine generated a good humoral response in rheumatoid patients, although lower than in healthy controls. The response was not affected by the use of prednisone or DMARDs.